(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: The mother of a high risk neonate is confronted with numerous parenting challenges, not the least of which is the decision about how to nourish her vulnerable newborn. Successful breastfeeding depends on overcoming obstacles posed by neonate’s condition, maternal health, and intensive care unit environment. Objective: to assess the competency on breastfeeding among mothers of high risk babies and practice of nurses in assisting the mothers in selected Intensive Care Unit, AIMS, Kochi, with a view to develop a nursing care protocol. Methodology: The descriptive research design was adopted and non-probability convenience sampling technique was used to collect data from 40 mothers by using structured questionnaire and observational checklists to assess the practice of mothers and staff nurses in NICU. Results: The study reveals that 22 (55%) mothers were having average knowledge and most of the mothers 23 (57.5%) had poor practice regarding the breastfeeding of the high risk neonate in NICU. Most of the staff nurses (50%) had average level of practice while assisting the mothers during breastfeeding in NICU. There is significant association between knowledge and demographic variables like education of the mother, order of pregnancy and source of knowledge. Conclusion: The nursing protocol was implemented and established a comprehensive improvement in the knowledge, care, support and management. Thus, the health care professional ultimately work towards providing a positive impact on the lives of high risk neonate.